SEEING THROUGH: THE MIRROR AS RELIGIOUS SYMBOL - Courtney, Charles (Journal of Dharma, 1981)
With mirrors we can see what is behind us, what is around the corner, what is far away, and most interesting, what we could not see at all otherwise, namely, ourselves. Whether mirrors have been pools of water, polished metal discs, or silvered glass, they seem to have always been an important part of human life. Mirrors help us gain knowledge, they create fear in those unacquainted with them, they can be tools of intrigue, they can be playthings, they can be objects of great beauty.